ANALISIS KESIAPAN KERJA SISWA SMK NEGERI 2 KOTA BIMA DI ERA REVOLUSI INDUSTRI 4.0 - Irwansya; Syahrul; Abdul Muis Mapalotteng (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2021)
This study aims to discover the partial and simultaneous influence of students' knowledge, work attitude, vocational competence, and learning motivation on students' work readiness. The study was a quantitative research with a descriptive approach using a survey method. The research sample was 54 respondents from the TKJ and Multimudia Department. The sampling technique employed purposive random sampling, namely sampling based on certain criteria. The results show that the work readiness of grade XII TKJ and Multimedia at SMK Negeri 2 in Bima City in the industrial revolution 4.0 era is in good category by 68.5%, students’ knowledge is in good category by 53.7% with work attitude by 68.5%, vocational competence is in high category by 72.2% and learning motivation is in 64.8%. The simple linear regression analysis shows that there is no influence of TKJ and Multimedia students' knowledge on work readiness ρ=0.34>0.05, correlation determinant r=0.346 (low), contribution of influence 1.7%, work attitude has a significant influence on work readiness proven by a contribution of 10.4% and is supported by a correlation value of r=0.322. The sstudents’ vocational competence of SMK Negeri 2 in Bima City in grade XII of TKJ and Multimedia has no significant influence on work readiness. The learning motivation has a significant influence on students' work readiness with a contribution of 12.6%. Multiple linear regression shows that there is a simultaneous significant influence of students’ knowledge, work attitude, vocational competence, learning motivation on work readiness with a contribution of 17.8%.